2023
DOI: 10.3389/fnut.2023.1117558
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and mortality risk of low skeletal muscle mass in critically ill patients: an updated systematic review and meta-analysis

Hui Yang,
Xi-Xi Wan,
Hui Ma
et al.

Abstract: BackgroundPatients with critical illness often develop low skeletal muscle mass (LSMM) for multiple reasons. Numerous studies have explored the association between LSMM and mortality. The prevalence of LSMM and its association with mortality are unclear. This systematic review and meta-analysis was performed to examine the prevalence and mortality risk of LSMM among critically ill patients.MethodsThree internet databases (Embase, PubMed, and Web of Science) were searched by two independent investigators to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…Our study found 40.6% of patients with unadjusted low calf circumference, increasing to 64.9% after adjusting for adiposity. These results align with a meta‐analysis showing 51.0% with low skeletal muscle mass at ICU admission, primarily by CT evaluation 1 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study found 40.6% of patients with unadjusted low calf circumference, increasing to 64.9% after adjusting for adiposity. These results align with a meta‐analysis showing 51.0% with low skeletal muscle mass at ICU admission, primarily by CT evaluation 1 …”
Section: Discussionsupporting
confidence: 88%
“…Low muscle mass is a common finding in critically ill patients at intensive care unit (ICU) admission 1 . This condition has emerged as an independent predictor of adverse outcomes, including higher rates tracheostomy 2 and extubation failure, 3 fewer ventilator‐free and ICU‐free days, 4 prolonged ICU and hospital length of stay (LOS), 2 and higher mortality risk 1 …”
Section: Introductionmentioning
confidence: 99%